The - Spratt, Mary (Cambridge University Press, 2000)
In addition to the traditional emphasis at this level on skills development, The Cambridge CAE Course focuses on other areas of language such as pronunciation, vocabulary extension, functional language and style. The Self-study Student's Book contains introductory notes on the CAE papers and self-study techniques, together with annotated keys and tapescripts